PENGARUH TINGKAT PENDIDIKAN, UMUR, JUMLAH TANGGUNGAN KELUARGA, PENDAPATAN SUAMI DAN MOTIVASI TERHADAP KEPUTUSAN WANITA UNTUK BEKERJA DI KECAMATAN KOTO SALAK KABUPATEN DHARMASRAYA - Bella Aulia Epinda; Anso Fino; Putri Melizasari (Horizon, 2021)
This study aims to analyze 1) the effect of education level, 2) the effect of age, 3) the influence of the number of family dependents, 4) the influence of husband's income and 5) the influence of motivation on women's decisions to work in Koto Salak District, Dharmasraya Regency. This research is focused on the influence of education level, age, number of dependents, husband's income and motivation on women's decision to work in Koto Salak Subdistrict, Dharmasraya Regency. The research method uses descriptive method. The results of the study show that: It can be seen that the results obtained are statistical> F table or 8.84> 2.38, so the decision H0 is rejected and Ha is accepted. So the variables of education level, age, number of family dependents, husband's income, motivation together have a significant effect on women's decisions to work.